2005
DOI: 10.1038/sj.bjp.0706188
|View full text |Cite
|
Sign up to set email alerts
|

Effects of amantadine and budipine on antidepressant drug‐evoked changes in extracellular 5‐HT in the frontal cortex of freely moving rats

Abstract: 1 Evidence has recently suggested that NMDA receptors may play a role in the aetiology and possible treatment of depression and that weak noncompetitive NMDA receptor antagonists such as amantadine can synergize with conventional antidepressants in a model of the illness. 2 To try to obtain a neurochemical rationale for these findings, we have studied the effects of acute and chronic administration of amantadine or the related drug budipine on cortical release of 5-hydroxytryptamine (5-HT) following the antide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…However, there are scarce data regarding the mechanisms by which NMDA antagonists augment the effects of antidepressants (e.g., paroxetine) in the FST. In this regard, using microdialysis, Owen and Whitton (2005) have interestingly demonstrated that acute administration of noneffective doses of the NMDA antagonist amantadine combined with noneffective doses of various antidepressants including paroxetine, reboxetine, budipine, and clomipramine increases the cortical release of 5-HT in freely moving rats. They also showed that chronic administration of amantadine at different times could increase the 5-HT release evoked by antidepressants and even the time required for significant increases in cortical 5-HT was reduced (Owen and Whitton 2005).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, there are scarce data regarding the mechanisms by which NMDA antagonists augment the effects of antidepressants (e.g., paroxetine) in the FST. In this regard, using microdialysis, Owen and Whitton (2005) have interestingly demonstrated that acute administration of noneffective doses of the NMDA antagonist amantadine combined with noneffective doses of various antidepressants including paroxetine, reboxetine, budipine, and clomipramine increases the cortical release of 5-HT in freely moving rats. They also showed that chronic administration of amantadine at different times could increase the 5-HT release evoked by antidepressants and even the time required for significant increases in cortical 5-HT was reduced (Owen and Whitton 2005).…”
Section: Discussionmentioning
confidence: 98%
“…In this regard, using microdialysis, Owen and Whitton (2005) have interestingly demonstrated that acute administration of noneffective doses of the NMDA antagonist amantadine combined with noneffective doses of various antidepressants including paroxetine, reboxetine, budipine, and clomipramine increases the cortical release of 5-HT in freely moving rats. They also showed that chronic administration of amantadine at different times could increase the 5-HT release evoked by antidepressants and even the time required for significant increases in cortical 5-HT was reduced (Owen and Whitton 2005). Therefore, taking these results together with our present data into consideration, it could be suggested that the antidepressantlike effects of combined noneffective doses of NMDA antagonists and paroxetine may be due to their effects on the central 5-HT release.…”
Section: Discussionmentioning
confidence: 98%
“…Owen and Whitton (2005) reported recently that amantadine and budipine (the weak NMDAR-As) given acutely with known antidepressants elevated extracellular serotonin concentration in the frontal cortices of rats and facilitated and potentiated this effect after prolonged treatment. These authors suggested that effects on serotonin concentrations could be due to a number of reasons, including alteration of glutamatergic tone at NMDARs that could facilitate serotonin neurotransmission as well as budipine and amantadine effects on monoamine metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Assuming the close linkage of oxidative stress and the pathophysiology of anxiety, depression, and pain, we evaluated oxidative parameters in the liver, kidney and cerebral cortex of mice exposed to acute and subchronic treatments. Of particular importance, VE‐ME treatment decreases TBARS levels, reducing the lipid peroxidation levels.…”
Section: Discussionmentioning
confidence: 99%